Comparison of clinical outcome of adjuvant chemotherapy between right and left colon Cancer - Kanaan, Marmar Samea; Abedallaa, Nader; Akel, Samer (Journal of medical and pharmaceutical sciences, 2022)
Objective: Colon cancer is currently divided into right colon cancer and left colon cancer, which differ from each other in characteristics, prognosis, and overall survival rate. The role of the primary tumor location in the cases of adjuvant therapy has not been clearly established in colon cancer. Therefore, this study was conducted, and the aim was to study the effect of the primary tumor location on overall survival (OS) and disease-free survival (DFS) by stage, after receiving adjuvant chemotherapy. Patients and Methods: We conducted a retrospective study on 327 stage II and III colon cancer patients, who received adjuvant chemotherapy after surgery at the Oncology Center of Tishreen University Hospital between January 2012 and September 2016. The patients’ ages ranged from 27 to 80 years. They were classified according to the location of the tumor into two groups: right colon cancer RCC (140 patients) and left colon cancer LCC (187 patients). According to the stage: stage II (201 patients) and stage III (126 patients). It was documented that any tumor recurrence or death occurred within a maximum period of five years from the date of diagnosis. Then, OS and DFS were compared between right and left colon cancer according to the stage in these patients. Results: There was no significant difference in the 5-year OS rate between RCC patients and LCC patients, and the 5-year DFS rate was better in RCC patients compared to LCC patients. In stage II: the five-year OS rate was (68.9%) for RCC patients versus (62%) for LCC patients (p-value = 0.08), while the five-year DFS rate was (66.2%) for RCC patients versus (49, 6%) for LCC patients (p-value=0.0001). In stage III: the five-year OS rate was (43.9%) for RCC patients versus (55%) for LCC patients (p-value=0.04). and the five-year DFS rate was (40.9%) for RCC patients versus (56.7%) for LCC patients (p-value=0.001). Conclusions: Both tumor location and stage had an effect on OS and DFS in our study patients, as RCC was associated with OS and DFS better than LCC in stage II patients, and worse than it in stage III patients, after adjuvant chemotherapy.